Risks of Squamous Cell Carcinoma of The Lip and Cutaneous Melanoma in Older Australians Using Hydrochlorothiazide (HTCZ) - Benjamin Daniels; Sallie-Anne Pearson; Claire M Vajdic; Anton Pottegård; Nicholas A Buckley; Helga Zoega (International Journal of Population Data Science, 2020)
Introduction HCTZ is first-line treatment for hypertension and among the most commonly used medicines in Australia. Recent evidence suggests increased risks of lip and skin cancers in association with HCTZ use.